GlycoPEGylated recombinant factor IX for hemophilia B in context - Santagostino E; Mancuso ME (Dove Medical Press, 2018)
Elena Santagostino, Maria Elisa Mancuso Angelo Bianchi Bonomi Hemophilia and Thrombosis Center, IRCCS Ca’ Granda Foundation, Maggiore Hospital Policlinic, Milan, Italy Abstract: Decisions over hemophilia treatment selection and switching involve balancing many clinical and patient-related factors. The current standard of care for patients with hemophilia B is prophylaxis with plasma-derived or recombinant factor IX (rFIX) concentrates. However, several extended half-life (EHL) rFIX products have recently been developed to improve treatment convenience and clinical outcomes for these patients. Nonacog beta pegol, an rFIX product that combines the FIX protein with a 40 kDa polyethylene glycol moiety, has been evaluated in 115 previously treated patients with hemophilia B (including 25 children) in the paradigm clinical trial program. FIX activity levels and pharmacokinetics were monitored throughout these trials and showed that nonacog beta pegol offers significant pharmacological improvements over standard FIX products. Once-weekly prophylaxis with nonacog beta pegol 40 IU/kg resulted in fewer bleeds in all patients (median annualized bleeding rate of 1.0 across all ages), resolved 90% of target joints, and improved health-related quality of life. No patients developed FIX inhibitors, and there were no thromboembolic events or unexpected safety concerns. Nonacog beta pegol was also safe and effective in the perioperative setting. These findings show that nonacog beta pegol is highly effective, while also offering more convenient dosing than standard FIX products. Nonacog beta pegol represents a significant advance in the current context of treatment for hemophilia B, offering effective management across several treatment modalities and settings, and potentially easing the treatment burden for patients of all ages. Meanwhile, the development of novel treatment strategies, such as gene therapy, anti-tissue factor pathway inhibitor antibodies, and RNA interference therapy, may provide patients with additional therapeutic options, which would require reassessment of the role of EHL products in the future. Keywords: long-acting FIX, PEGylated rFIX, extended half-life, prophylaxis